STUDI ANALISIS PERSEPSI MAHASISWA TERHADAP ISU-ISU KONTEMPORER (MULTIKULTURALISME) DALAM PERKULIAHAN ILMU PENDIDIKAN ISLAM DI IAIN CURUP - Siti Bariroh Alkhofifah; Sabarudin Sabarudin; Deri Wanto (Al-Mabsut: Jurnal Studi Islam dan Sosial, 2022)
Abstract: Multiculturalism is an attitude that must be owned by every individual who lives on this earth. One of the efforts to instill multiculturalism is through education that has been implemented in schools and colleges. The challenge faced is that not all education actors, namely educators and students, have the same understanding of multicultural education. Therefore, students of the tarbiyah and teacher training faculties, especially students of Islamic Education in the Islamic Education Sciences course, need to understand multicultural education and its application. This study uses a qualitative approach with a case study method, where the researcher reveals the perceptions of IAIN Curup students on contemporary issues that focus on multiculturalism education in learning. All data were collected through questionnaires and interviews to obtain results in accordance with the objectives of this study. From the results of the study obtained information that most of the students of Islamic Education in Islamic Education subjects individually have a very good perception of the implementation of multicultural education. Factors driving student perceptions of multiculturalism awareness include strengthening similarities in differences, mutual trust and understanding, and tolerance. Furthermore, for educators there is a need for improvement in learning and guidance that supports student multicultural activities.  Keywords: Multiculturalism, Islamic Education, Student Perceptions